2017
DOI: 10.1093/nar/gkx1180
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl isomerization of the CENP-A N-terminus regulates centromeric integrity in fission yeast

Abstract: Centromeric identity and chromosome segregation are determined by the precise centromeric targeting of CENP-A, the centromere-specific histone H3 variant. The significance of the amino-terminal domain (NTD) of CENP-A in this process remains unclear. Here, we assessed the functional significance of each residue within the NTD of CENP-A from Schizosaccharomyces pombe (SpCENP-A) and identified a proline-rich ‘GRANT’ (Genomic stability-Regulating site within CENP-A N-Terminus) motif that is important for CENP-A fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 54 publications
(72 reference statements)
0
35
0
Order By: Relevance
“…In our previous investigation into the role of the SpCENP-A NTD, we assessed the importance of the proline residues residing in the GRANT motif by overexpressing a mutant SpCENP-A cnp1-4PA bearing alanine mutations at four proline residues (P10AP13AP15AP17A). We found that the SpCENP-A cnp1-4PA mutant was almost as stable as the wild-type protein in a protein turnover assay [ 28 ]. These observations suggested that the ‘GRANT-proline’ residues have no effect on the proteasome-associated turnover of SpCENP-A protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous investigation into the role of the SpCENP-A NTD, we assessed the importance of the proline residues residing in the GRANT motif by overexpressing a mutant SpCENP-A cnp1-4PA bearing alanine mutations at four proline residues (P10AP13AP15AP17A). We found that the SpCENP-A cnp1-4PA mutant was almost as stable as the wild-type protein in a protein turnover assay [ 28 ]. These observations suggested that the ‘GRANT-proline’ residues have no effect on the proteasome-associated turnover of SpCENP-A protein.…”
Section: Resultsmentioning
confidence: 99%
“…The localization of CENP-A to centromeric regions is dependent on a CENP-A-targeting domain (CATD) nested within the histone fold domain of CENP-A, which interacts with the CENP-A loading factor Holliday Junction Recognition Protein (HJURP) and stabilizes CENP-A–histone H4 interaction [ 36 , 37 ]. Recently, it has been shown by us and others that the flexible NTD tail of CENP-A directs CENP-A centromeric targeting independently of the CATD via binding with CENP-A loading factors such as Sim3/Nuclear Autoantigen Sperm Protein (NASP) [ 28 , 38 ], the CCAN component CENP-T [ 39 ], and CENP-B [ 28 , 40 ]. We have further shown that the Sim3–SpCENP-A interaction is mediated via prolyl cis – trans isomerization of a proline-rich GRANT motif within the SpCENP-A NTD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…could not be identified when Cse4 was used as a query in BLAST search. In fission yeast, the proline-rich motif GRANT ( g enomic stability- r egulating site within CENP- A N - t erminus) is essential for centromeric targeting of Cnp1 [ 29 ]. A proline-rich GRANT motif was found in the N-terminal region of CENP-A L.s.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published procedures were followed closely [ 55 , 56 ]. Briefly, log-phase growing cultures (OD 600nm = 0.5) were fixed with 3% paraformaldehyde (Sigma-Aldrich, St Louis, MO, USA) before homogenization with glass beads.…”
Section: Methodsmentioning
confidence: 99%